Role of metabolic characteristics in the co-occurrence of insomnia, Alzheimer’s disease, and Parkinson’s disease: a Mendelian randomization study - Liu, Chengyong; Wang, Chi; Jiang, Jing; Bo, Yuyang; Nan, Lixiu; Zhang, Ying; Zhu, Kongxi; Wang, Xiaoqiu; Feng, Xinxin; Lian, Xiaoyang; Qin, Shan (Frontiers in Aging Neuroscience, 2025)
ObjectiveThere reportedly exists a significant comorbidity between insomnia and neurodegenerative diseases, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD), indicative of a potential link to serum metabolic dysregulation.MethodTo elucidate shared pathophysiological mechanisms between insomnia and AD/PD, we performed comprehensive two-sample Mendelian randomization (MR) analyses, investigating 1,400 serum metabolic characteristics for their causal relationships with the risks of insomnia, AD, widely defined AD (WDAD), and PD. We employed publicly available genetic data; the primary estimate was determined using inverse-variance weighting, supplemented by weighted median, simple mode, weighted mode, and the MR-PRESSO and MR-Egger methods to evaluate heterogeneity and pleiotropy.ResultsThe ratio of N-palmitoyl-sphingosine to N-palmitoyl-sphinganine is linked to higher risks of insomnia (OR = 1.137, 95% CI = 1.015–1.273, p = 0.026) and AD (OR = 1.090, 95% CI = 1.005–1.183, p = 0.037). The acetylcarnitine to propionylcarnitine ratio is a risk factor for insomnia (OR = 1.190, 95% CI = 1.003–1.370, p = 0.016) but has protective effects against AD (OR = 0.868, 95% CI = 0.784–0.961, p = 0.006) and WDAD (OR = 0.892, 95% CI = 0.817–0.973, p = 0.010). Glutamine conjugate of C7H12O2 levels are associated with reduced risk of insomnia (OR = 0.863, 95% CI = 0.749–0.995, p = 0.042) and PD (OR = 0.856, 95% CI = 0.746–0.981, p = 0.026).ConclusionOur findings highlight the crucial role of serum metabolic characteristics in the comorbidity of insomnia with neurodegenerative diseases, providing valuable insights into prospective therapeutic targets and diagnostic markers.